Implementasi Perancangan Desain UI/UX pada Sistem Informasi Berbasis Website SMPN 3 Pacet (Current Research in Education: Conference Series Journal, 2023)
An information system is a combination of human and computer activities to produce a product that contains a collection of information. The information system on the SMPN 3 Pacet website is a collection of information to introduce to the public about the SMPN 3 Pacet school, in the development of a User interface (UI) and user experience (UX) planning is an important stage. The UI/UX appearance gives an initial impression to potential users. This article describes how the UI/UX is designed on the SMPN 3Pacet website using the Human Centered Design HCD approach. This study aims to implement user interface planning for information systems based on the SMPN 3 Pacet website. The final result in this study is the high fidelity design of the SMPN 3 Pacet website information system and how effective and efficient it is to use the website for use by users. The research process consists of several stages, namely making a user interface design using Human Centered Design (HCD), which focuses on all users in the data collection process as well as the evaluation process of the design that is being made, and if necessary redesign can be done.